Stability of Structures - Principles and Applications - Yoo, Chai Hong; Lee, Sung Chil (Elsevier, 2011)
The current trend of building more streamlined structures has made stability analysis a subject of extreme importance. It is mostly a safety issue because stability loss could result in an unimaginable catastrophe. Written by two authors with a combined 80 years of professional and academic experience, the objective of this book is to provide engineers and architects with a firm grasp of the fundamentals and principles that are essential to performing effective stability analysts. Concise and readable, this guide presents stability analysis within the context of elementary nonlinear flexural analysis, providing a strong foundation for incorporating theory into everyday practice. Although the book is primarily devoted to analysis, rudimentary design aspects are discussed.